Namaste Care in nursing care homes for people with advanced dementia: protocol for a feasibility randomised controlled trial. Issue 11 (25th November 2018) - Froggatt, Katherine; Patel, Shakil; Perez Algorta, Guillermo; Bunn, Frances; Burnside, Girvan; Coast, Joanna; Dunleavy, Lesley; Goodman, Claire; Hardwick, Ben; Kinley, Julie; Preston, Nancy J; Walshe, Catherine
Abstract : Introduction: Many people living with advanced dementia live and die in nursing care homes. The quality of life, care and dying experienced by these people is variable. Namaste Care is a multisensory programme of care developed for people with advanced dementia. While there is emerging evidence that Namaste Care may be beneficial for people with dementia, there is a need to conduct a feasibility study to establish the optimum way of delivering this complex intervention and whether benefits can be demonstrated in end-of-life care, for individuals and service delivery. The aim of the study is to ascertain the feasibility of conducting a full trial of the Namaste Care intervention. Methods and analysis: A feasibility study, comprising a parallel, two-arm, multicentre cluster controlled randomised trial with embedded process and economic evaluation. Nursing care homes (total of eight) who deliver care to those with advanced dementia will be randomly allocated to intervention (delivered at nursing care home level) or control. Three participant groups will be recruited: residents with advanced dementia, informal carers of a participating resident and nursing care home staff. Data will be collected for 6 months. Feasibility objectives concern the recruitment and sampling of nursing homes, residents, informal carers and staff; the selection and timing of primary (quality of dying and quality of life) and secondary clinical outcome measures (person centredness, symptom presence, agitation, quality of life, resource use and costs and residents' activity monitored using actigraphy). Acceptability, fidelity and sustainability of the intervention will be assessed using semistructured interviews with staff and informal carers. Ethics and dissemination: This protocol has been approved by NHS Wales Research Ethics Committee 5 (ref: 17/WA0378). Dissemination plans include working with a public involvement panel, through a website (http://www.namastetrial.org.uk ), social media, academic and practice conferences and via peer reviewed publications. Trial registration number: ISRCTN14948133 ; Pre-results.